The generation of human innate lymphoid cells is influenced by the source of hematopoietic stem cells and by the use of G‐CSF. Issue 5 (19th February 2016) - Moretta, Francesca; Petronelli, Francesca; Lucarelli, Barbarella; Pitisci, Angela; Bertaina, Alice; Locatelli, Franco; Mingari, Maria Cristina; Moretta, Lorenzo; Montaldo, Elisa
Abstract : Pre‐ and post‐HSCT treatments may affect the differentiation of HSCs towards innate lymphoid cells (ILCs). Here we show that HSCs exposed to G‐CSF display a reduced ILC differentiation potential. In particular, HSCs mobilized from good G‐CSF responder donors yield the lowest ILC recovery among all HSC sources analyzed. Abstract : NK cells play a central role in the haploidentical HSC transplantation (HSCT) to cure high‐risk leukemias. Other innate lymphoid cells (ILCs) have been proposed to exert a protective role in graft‐versus‐host disease and could also contribute to anti‐microbial defence and to lymphoid tissue remodeling. Thus, we investigated the ILC differentiation potential of HSCs isolated from BM, mobilized peripheral blood (PB), and umbilical cord blood (UCB). BM CD34 + cells are enriched in lymphoid‐committed precursors, while PB CD34 + cells preferentially contain myeloid precursors. In vitro differentiation experiments revealed that the highest and the lowest CD56 + CD161 + ILC recovery was detected in UCB and PB HSC cultures, respectively. Among CD56 + CD161 + ILCs, the ratio between NK cells and ILC3s was similar for all HSC analyzed. ILC recovery in PB CD34 + cultures was lower for G‐CSF‐mobilized HSCs (good mobilizers) than for G‐CSF+plerixafor‐mobilized HSC (poor mobilizers). Moreover, G‐CSF inhibited in vitro ILC recovery and the degree of inhibition was proportional to the time of exposure to the cytokine. Thus, although all common sources of HSC for transplant differentiate towards ILCs, substantial differences exist among different sources and G‐CSF may influence ILC recovery. These data offer new clues for a better understanding of the immune reconstitution after HSCT.